POTENSI ANTIINFLAMASI SENYAWA BIOAKTIF DARI SYZYGIUM MYRTIFOLIUM: STUDI MOLECULAR DOCKING BERTARGET COX-2 - Putri, Refsya Azanti; Saputra, Muhammad Yogi; Enggelina, Nia Natalia; Windasari, Liska; Ivansyah, Atthar Luqman (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Chronic inflammation contributes significantly to various degenerative diseases, with Cyclooxygenase-2 (COX-2) being a central target for anti-inflammatory drug development. Syzygium myrtifolium, a native Indonesian plant, is known to contain a variety of bioactive compounds with pharmacological potential. This study aims to investigate the anti-inflammatory activity of S. myrtifolium active compounds on COX-2 using a molecular docking approach. The tested compounds include avicularin, betulinic acid, ursolic acid, and two flavanones modeled and docked against the COX-2 protein (PDB ID: 5F19) using YASARA. Docking simulations were performed using YASARA software via a blind docking method and visualized through Discovery Studio. The results revealed that four compounds demonstrated stronger binding affinity than celecoxib, with (2S)-7-Hydroxy-5-methoxy-6,8-dimethylflavanone showing the most stable interaction with 9.0450 kcal/mol binding energy. Toxicity prediction suggests these compounds are generally safe based on LD50 values and toxicity class. These findings support the potential of S. myrtifolium as a natural source of COX-2 inhibitors.